Optimasi Pengiriman Bahan Baku pada Perusahaan Menggunakan Metode North West Corner - Maryanah; Ardian Dwi Praba (Jurnal Teknik, 2026)
Raw material delivery is a recurrent logistics decision that directly affects production continuity and total operating cost. This paper formulates the delivery planning task as a balanced transportation problem, where multiple supply points deliver a single commodity to multiple demand points under known unit transportation costs. The North-West Corner (NWC) method is applied to construct an initial basic feasible solution quickly and systematically. Using a dummy case with three origins and four destinations, the paper shows the allocation process step by step, updates remaining supply and demand in each iteration, and computes the resulting total transportation cost. The results demonstrate how NWC can provide a feasible allocation with transparent calculations suitable for operational planning and as a starting point for further optimality tests. The discussion highlights the practical interpretation of the allocation matrix, the conditions for balanced/unbalanced problems, and the method’s limitations because it does not consider cost during the initial allocation. Keywords: Transportation Optimization, Raw materials, NWC